THE EFFECT OF HALAL AWARENESS AND FOOD INGREDIENTS ON CONSUMER INTERESTS OF CULINARY SEAFOOD BEACH TOURISM - Najmudin Najmudin; Syihabudin Syihabudin; Ahmad Fatoni (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri (UIN), 2021)
This study aims to determine (1). The effect of halal awareness on consumer buying interest in coastal tourism seafood culinary SMEs. (2). The influence of foodstuffs on consumer buying interest in coastal tourism seafood culinary SMEs. And (3). The influence of halal awareness and foodstuffs on consumer buying interest in coastal tourism seafood culinary SMEs. The object of this research is the culinary consumers of Seafood Kedaikita in Gope beach. The research method used is a quantitative method. The data collection method used a questionnaire. Data were analyzed using multiple linear regression method. The results of this study indicate that (1). Halal awareness affects the buying interest of consumers of beach tourism culinary SMEs. Shown by the value of t is greater than t table (6,851 1. 668) and the significance value is smaller than the alpha value (0.000 0.05) (2). Foodstuffs affect consumer buying interest in coastal tourism culinary SMEs. Shown by the value of t count greater than t table (5.784 1.668) and the significance value is smaller than the alpha value (0.000 0.05). (3). Halal awareness and food ingredients have a positive and significant effect on the purchase interest of consumers of coastal tourism culinary SMEs. Shown by the value of F count greater than F table (32,930 3.12) and the significance value is smaller than the alpha value (0.000 0.05) 0.05). (3). Halal awareness and food ingredients have a positive and significant effect on the purchase interest of consumers of coastal tourism culinary SMEs. Shown by the value of F count greater than F table (32,930 3.12) and the significance value is smaller than the alpha value (0.000 0.05) 0.05). (3). Halal awareness and foodstuffs have a positive and significant effect on the purchase interest of consumers of coastal tourism culinary SMEs. Shown by the value of F count greater than F table (32,930 3.12) and the significance value is smaller than the alpha value (0.000 0.05)